Setor sucroalcooleiro: regime jurídico ambiental das usinas de açúcar e álcool - Moraes, Rodrigo Jorge (2009)
This paper intents to study the alcohol and sugar sector, its history, development, relations with the state and the society, regarding the analysis on the law regime applicable to the alcohol and sugar plants and, specifically, the close relation between this activity and the environmental issue